Low Tidal Volume Positive End-Expiratory Pressure versus High Tidal Volume Zero-Positive End-Expiratory Pressure and Postoperative Pulmonary Functions in Robot-Assisted Laparoscopic Radical Prostatectomy - Haliloglu, Murat (Med Princ Pract, 2018)
OBJECTIVE: The aim was to compare the effects of low tidal volume (V(T)) and moderate positive end-expiratory pressure (PEEP) with high V(T) and zero end-expiratory pressure (ZEEP) on postoperative pulmonary functions and oxygenation in patients undergoing robot-assisted laparoscopic radical prostatectomy. SUBJECTS AND METHODS: Forty-four patients were randomized into low V(T)-PEEP and high V(T)-ZEEP groups. The patients were ventilated with a V(T) of 6 mL/kg and 8 cm H(2)O PEEP in the low V(T)-PEEP group and a V(T) of 10 mL/kg and 0 cm H(2)O PEEP in the high V(T)-ZEEP group. Preoperative and postoperative spirometric measurements were done and chest X-rays were evaluated using the radiological atelectasis score (RAS). p < 0.05 was considered statistically signiﬁcant. RESULTS: The intraoperative and postoperative arterial partial pressure of oxygen and arterial oxygen saturation values were significantly higher in the low V(T)-PEEP group than in the high V(T)-ZEEP group. At all times, the arterial-to-alveolar oxygenation gradients were significantly lower in the low V(T)-PEEP group than in the high V(T)-ZEEP group. Preoperative RAS were similar in both groups, but the postoperative RAS was significantly lower in the low V(T)-PEEP group (p < 0.001). Forced vital capacity, forced expiratory volume in 1 s, and peak expiratory flow rate recorded postoperatively were significantly lower in the high V(T)-ZEEP group (p < 0.001). CONCLUSIONS: Postoperative pulmonary functions were less impaired in patients ventilated with a V(T) of 6 mL/kg and 8 cm H(2)O PEEP than in patients ventilated with a V(T) of 10 mL/kg and ZEEP.